ความสามารถในการเผชิญและฟันฝ่าอุปสรรคของนิสิตนักศึกษา คณะสัตวแพทยศาสตร์ชั้นปีที่ 6 ในประเทศไทย - อรรถพล ระวิโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this research were to study the Adversity Quotients (AQ) of the 6th year Veterinary students in Thailand and to identify factors related to the AQ. There were 328 returned questionnaires out of 498 sent out giving 66.3% response rate. Veterinarians’ Professional Expectation and Adversity Quotients Questionnaires were the main instruments used. The data were described using standard descriptive statistics. Relationships between factors and the AQ were analyzed using Multiple Linear Regression Analysis. The results revealed that the average of the Veterinarians’ Professional Expectation in total was at high level in both Work’s Content Expectation and Quality of Work’s Life Expectation. The average of the AQ in total was at medium to high level. By bivariate correlation, domiciles and the Veterinarians’ Professional Expectation were positively and significantly related to the AQ at r = 0.109 (p = 0.05) and r = 0.222 (p = 0.01) respectively. Only was Veterinarians’ Professional Expectation independently associated with the AQ by multiple regression analysis. The prediction function derived from the analysis was as follow: YAdversity Quotient = 97.51+0.28(Veterinarians’ Professional Expectation)